2022
DOI: 10.1155/2022/7526826
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Quantitative Assessment of Impact Damage of Yellow Peaches Using the Combined Hyperspectral Technology and Mechanical Parameters

Abstract: The quantitative description of the impact damage of yellow peaches is an essential basis for evaluating their quality and guiding their postharvest handling. In this study, the combined hyperspectral technology and mechanical parameters method were used to quantitatively investigate the impact damage of yellow peaches. Firstly, the mechanical parameters, which are damaged area, absorbed energy, maximum contact force, and maximum stress of yellow peaches, were obtained by the impact device. The statistical reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…When these values were reached, the storage test was stopped. Therefore, fragrant pears were stored for 0, 5,10,15,20,25,30,35, and 40 days, and their hardness and SSC were measured every five days. A total of 1260 fragrant pears were needed for the storage test.…”
Section: Storage Tests Of Korla Fragrant Pearsmentioning
confidence: 99%
See 1 more Smart Citation
“…When these values were reached, the storage test was stopped. Therefore, fragrant pears were stored for 0, 5,10,15,20,25,30,35, and 40 days, and their hardness and SSC were measured every five days. A total of 1260 fragrant pears were needed for the storage test.…”
Section: Storage Tests Of Korla Fragrant Pearsmentioning
confidence: 99%
“…They discovered that, as storage temperature and impact strength increased, banana hardness decreased, weight loss rate increased, and peel brightness decreased significantly. Zhang et al [15] carried out impact damage tests on yellow peaches, releasing samples from different angles based on the pendulum principle to obtain samples with different damage degrees. Because of the swing angle and traction line shaking, the fruits rotate.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, mechanical parameters such as maximum stress, maximum force, absorbed energy, damage area, restitution coefficient, bruise susceptibility, and damage depth are used to characterize the extent of impact damage to fruit. [5][6][7] Stropek et al 8 designed a fruit collision device based on the principle of the single pendulum, and those mechanical parameters such as maximum stress, maximum force, impact time, maximum deformation, and restitution coefficient of the pear during the collision were obtained. The results of the study found that the maximum stress and permanent deformation were most suitable for characterizing the degree of impact damage of pear.…”
Section: Introductionmentioning
confidence: 99%
“…The damage energy usually decreases with storage time and fruit maturity, indicating that energy is a suitable and easy measurable parameter to evaluate the degree of damage. In terms of fruit impact damage, researchers evaluated the damage degree of apples [23,24], palm fruit [25], yellow peaches [26], and pears [27], and revealed a relationship between impact height, contact material, impact damage volume, and impact energy, and obtained the surface pressure distribution of fruit under different energy free loads, as well as the critical energy value of pulp tissue damage. The damage resistance characteristics of fruit under the impact load of free fall were clarified.…”
Section: Introductionmentioning
confidence: 99%